Kajian Parameter Kimia Posfat di Perairan Danau Sentani Berwawasan Lingkungan - Auldry F. Walukow (Universitas Muhammadiyah Surakarta, 2010)
The Sentani Lake is located in Jayapura regency which at covered east Sentani, Sentani, and West Sentani districts. The Sentani Lake has problems. The first problem is high of erosion number 94.52 ton/ha/year that the value higher than value of erosi on tolerance number 25 ton/ha/year. Second problem is chemical pollution indicated by high concentration Cu (0,0201-0,1081 mg/L) and Zn (0,21-0,36 mg/L) Those concentration are exceeds water quality standard that approve by government in PP 82 Tahun 2001 about management water quality and water pollution control. There for is needed research and management for sustainable of Sentani Lake. The aims of this research are 1) to analyze about the pollution load Sentani Lake, and 2) to analyze the assimilation capacity Sentani Lake aquaculture. The research method are survey and experiment. Results from a research showed that the load of pollution from river is obtained as follow (each in ton/month) is Pospat (ranges between 0.57 to 4.74). The assimilation capacity from lake is obtained as follow (in ton.month) is Pospat (1.40). The load of pollution are upper of the assimilation capacity.